UPAYA PERBAIKAN STATUS GIZI BALITA MELALUI PROGRAM PENYULUHAN DI POSYANDU ANAK DI DESA SIREMEN KECAMATAN TANARA KABUPATEN SERANG - Permana, Angrian; Puspa, Rani; Juliana, Voni Dwi; Nuriah, Siti (Yayasan Education and Social Center, 2024)
The community service activities carried out aim to improve the nutritional status of toddlers in Siremen Village, Tanara District, Serang Regency. This village faces serious challenges related to malnutrition and malnutrition among children under five, which are caused by mothers' lack of knowledge about nutrition, unhealthy eating patterns, and limited access to nutritious food. In an effort to overcome this problem, a nutrition education program was carried out at the Siremen Village Children's Posyandu. This program includes providing information about a balanced diet, the importance of exclusive breastfeeding, and ways to prepare nutritious food with locally available ingredients. Through collaboration between health workers, posyandu cadres, and local government support, this outreach program is expected to be effective in increasing mothers' knowledge and awareness regarding the importance of good nutrition for their children. Thus, it is hoped that there will be positive changes in the behavior of mothers in providing food to their toddlers, which will ultimately result in an increase in the nutritional status of toddlers in Siremen Village. Periodic evaluations will be carried out to measure the effectiveness of the program, by monitoring various indicators including maternal knowledge about nutrition, nutritional status of toddlers, and changes in maternal behavior in providing food. It is hoped that the results of this activity can become a model for other villages in efforts to improve the nutritional status of children under five through a sustainable and comprehensive nutritional education program